Serum MDA, α-Tocopherol and β-Carotene Levels in Patients Having Hyperglycemic Glucose Metabolism Disorders - Ünalacak, Murat; Atmaca, Hulusi; Gürel, Ahmet; Armutcu, Ferah; Demircan, Nejat; Aktunç, Erol (Fırat University, 2005)
Objectives: Evaluation of serum MDA, α-tocopherol and β-carotene in patients having diabetes mellitus (DM), impaired glucose tolerance (IGT) and impaired fasting glucose (IFG). Materials and Methods: Ninety-nine patients, who were detected to have DM, IGT or IFG at their admission to Zonguldak Karaelmas University Hospital, Family Medicine or Internal Medicine outpatient clinics, and 37 healthy controls were included in the study. MDA, α-tocopherol and bcarotene levels were studied in the serum samples of all patients and controls. Results: While MDA level in DM group was significantly higher than the IGT, IFG and control groups, α-tocopherol level in DM group was lower than the control group and β-carotene level was lower than IGT, IFG and control groups. While MDA level in IGT group was significantly higher than the IFG and control groups, α-tocopherol level in IGT group was lower than the control group and β-carotene level was lower than IFG and control groups. There was no significant difference of any of the three parameters between IFG and control groups Conclusion: While lipid peroxidation increases, α-tocopherol and β-carotene levels decrease in the diseases with hyperglycemia, except IFG ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Diabetes mellitus (DM), bozulmuş glukoz toleransı (BGT) ve bozulmuş açlık glukozu (BAG) olan hastalarda serum MDA, α-tokoferol ve β-karoten düzeylerinin değerlendirilmesi. Gereç ve Yöntem: Zonguldak Karaelmas Üniversitesi Hastanesi Aile hekimliği ve Dahiliye polikliniklerine başvuran ve yapılan tetkiklerle DM, BGT ve BAG olduğuna karar verilen toplam 99 hasta ve 37 sağlıklı kontrol çalışmaya dahil edildi. Hasta ve kontrol gruplarına ait serum örneklerinde MDA, α -tokoferol ve b-karoten çalışıldı. Bulgular: DM grubunun MDA düzeyi BGT, BAG ve kontrol gruplarından anlamlı derecede yüksek bulunurken, α -tokoferol düzeyi kontrol grubundan, β-karoten düzeyi ise BGT, BAG ve kontrol gruplarından düşük bulundu. BGT grubunun MDA düzeyi BAG ve kontrol gruplarından anlamlı derecede yüksek bulunurken, α-tokoferol düzeyi kontrol grubundan, β-karoten düzeyi ise BAG ve kontrol gruplarından düşük bulundu. BAG grubu ile kontrol grubu arasında her üç parametre açısından da anlamlı fark yoktu. Sonuç: BAG hariç, diğer hiperglisemi ile seyreden hastalıklarda lipid peroksidasyonu artarken, α-tokoferol ve β-karoten seviyeleri düşmektedir. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Hiperglisemik Glukoz Metabolizma Bozukluğu Olan Hastalarda Serum Malondialdehit, α-Tokoferol ve - β- Karoten Düzeyleri